(untitled) (Research, Society and Development, 2022)
Ensiling is a forage conservation technique in times of favorable rainfall so that the silages produced can be offered in periods of scarcity of rain, in which the growth and productivity of forages are compromised. This technique is an alternative to mitigate the effects of seasonality of forage production on animal production. However, the lack of correct planning can make it difficult to use the technique and/or waste forage material with great potential for use. The relocation of silage aims to store the forage again without major damage to the quality of the material. In this way, the objective was to carry out a systematic study on the movement of silage from one place to another and its implications for the quality of the final product. Information on the parameters that affect the quality of the relocated silage was considered, such as the type of material to be ensiled, its nutritional composition, fermentative parameters and aerobic stability of the relocated silages. Such characteristics are directly related to the silage technique, that is, if any of the steps is not performed well, the quality of the silage will be compromised and the relocation process will also be impaired. Through the research carried out, it was found that silages relocated and stored for a longer period tend to reduce their nutritional value. The relocated material tends to lose aerobic stability due to nutrient degradation caused by contact with oxygen. In addition, the storage period after relocation is the variable that most influences the nutritional losses of relocated silages.